Determination of time cycle engines of devices used in locomotive repair - Dubinech, L. V.; Marenich, O. L.; Matko, A. N. (Science and Transport Progress, 2012)
Reasonability of determination the hour characteristics of engine cycle depending on peculiarities of technological process, which is executed with a help of certain equipment, is shown in the article. The corresponding methodology is given.